Business process quality measurement using advances in static code analysis - Ladányi Gergely (2015)
Business process models play an important role in the life of a company. Resemblances between software programs and business processes inspired several researchers to adapt software metrics from the field of static code analysis to help designers to build more effective and understandable processes. This paper aims to add recent advances in software quality measurement such as benchmarking and ISO/IEC 25010 standard based quality models to business process quality measurement. These techniques were proved to be very useful in software engineering both for managers and developers; moreover, they can be easily adopted to business process workflows. We focused on a specific type of flowchart called event-driven process chain (EPC), because in an EPC the activities are very often managed by software systems and our assumption is that the quality of these software systems affects the quality of the EPC itself. The presented business process quality model also uses the quality and test coverage metrics of these software systems besides business process metrics.
Keywords: Természettudományok; Számítás- és információtudomány